2010
DOI: 10.1387/ijdb.093056jp
|View full text |Cite
|
Sign up to set email alerts
|

Primitive erythropoiesis in the mammalian embryo

Abstract: Erythropoiesis in adult mammals is characterized by the progressive maturation of hematopoietic stem cells to lineage-specific progenitors, to morphologically identifiable precursors which enucleate to form mature erythrocytes. In contrast, primitive erythropoiesis is characterized by the appearance within the yolk sac of a transient, lineage-restricted progenitor population which generates a wave of erythroid precursors. These precursors undergo progressive maturation in the bloodstream, characterized by nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 99 publications
(55 reference statements)
0
65
0
1
Order By: Relevance
“…Mammalian erythroid cells originate from hematopoietic stem and progenitor cells. In the embryo and fetus, erythroid cells have differing developmental origins, with the primitive erythroid cell lineage developing from yolk sac-derived erythroid progenitors and the definitive cell lineage maturing from two different developmentally regulated stem and progenitor cell populations (67)(68)(69)(70). These cells have different programs of regulation, with variation in spatial, temporal, and site-specific differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Mammalian erythroid cells originate from hematopoietic stem and progenitor cells. In the embryo and fetus, erythroid cells have differing developmental origins, with the primitive erythroid cell lineage developing from yolk sac-derived erythroid progenitors and the definitive cell lineage maturing from two different developmentally regulated stem and progenitor cell populations (67)(68)(69)(70). These cells have different programs of regulation, with variation in spatial, temporal, and site-specific differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…62 Importantly, enucleation is not restricted to definitive erythroid cells; primitive yolk-sac derived erythropoiesis also exhibits chromatin condensation and enucleation. 63 While nuclear condensation is thought to be critical for mammalian enucleation, chromatin condensation also occurs in many other tissue types, including rather ubiquitous cellular processes, such as cell division and apoptosis. Apoptotic mechanisms, such as caspase activation, are known to be responsible for enucleation of lens epithelia and keratinocytes, although the process is not similar to enucleation of erythroid precursors.…”
Section: Histone Deacetylation and Erythroblast Enucleationmentioning
confidence: 99%
“…8 Although possible EPO production in renal tubular cells was reported previously 9, 10 a more recent study has shown that fibroblast-like cells in the corticomedullary interstitium of the kidney synthesize EPO, while tubular cells do not. 8 Proliferative effect of EPO on several progenitor cells including erythroid progenitor cells, [11][12][13] endothelial progenitor cells (EPC), 14,15 cardiomyogenic stem cells 37 has been reported. EPO is known to act specifically on haematopoietical cells, however recent evidence demonstrated several non-haematopoietical effects.…”
Section: Introductionmentioning
confidence: 99%
“…40 During embryo development, immature primitive erythroblasts begin to enter the bloodstream with the onset of cardiac contractions. 11 Ji et al 41 hypothesized that the timing of onset of heartbeat and erythroid cell migration are tightly coordinated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation